The sequoia-loving sprite, a new genus and species of fungus gnat (Diptera, Mycetophilidae) from California - Peter Kerr (ZooKeys, 2014)
California is one of the most biologically diverse regions of the world, yet the diversity of fungus gnats (Mycetophilidae) remains largely undocumented within the state. A modest survey of these flies has led to the discovery of a new genus and species of gnat that lives alongside one of the most iconic trees in the world, the giant sequoia (Sequoiadendron giganteum). Spritella sequoiaphila gen. et sp. n. is described and illustrated and its status among other mycetophilid genera is analyzed and discussed.